An Analysis of Tourism Development Based on Local Wisdom from the Perspective of Islamic Economics (Maqasid al-Shariah): A Case Study of Panorama Baru, Bukittinggi - Ahmad Rasyid; Rahmat Daim Harahap; Nursantri Ya (Jurnal Bisnis dan Manajemen, 2025)
This study aims to analyze the development of tourism based on local wisdom and its relevance to the principles of Maqashid Shariah from the perspective of Islamic economics. The primary focus of this research includes identifying local wisdom values aligned with the five main objectives of Maqashid Shariah: preservation of religion (hifzh al-din), life (hifzh al-nafs), intellect (hifzh al-‘aql), lineage (hifzh al-nasl), and wealth (hifzh al-mal). Additionally, the research explores how the development of tourism contributes to preserving Islamic values and local culture, as well as identifying the challenges and opportunities involved. The research uses a qualitative descriptive method with a case study approach in a tourism area rooted in local culture and traditions. Data were collected through observation, in-depth interviews, and documentation, and analyzed thematically. The results indicate that tourism development based on local wisdom not only enhances the economic well-being of the local community but also helps preserve religious, social, and cultural values. Local values such as mutual cooperation, respect for nature, and cultural preservation are shown to align with the objectives of Maqashid Shariah. However, challenges such as limited infrastructure and the risk of cultural commercialization persist. On the other hand, opportunities to develop Shariah-compliant tourism are significant, in line with increasing public awareness of ethical and sustainable tourism. This study recommends the integration of Maqashid Shariah principles into tourism development strategies as a balanced approach that supports both economic benefits and the preservation of Islamic and local cultural values.